Analysis of Rumen Microbial Population of Cattle Given Silage and Probiotics Using Terminal Restriction Fragment Length Polymorphism - RONI RIDWAN1; YANTYATI WIDYASTUTI1; SRI BUDIARTI; ACHMAD DINOTO (Indonesian Society for microbiology, 2009)
Rumen ecology is an important observation in evaluating the effectivity of silage and probiotic additives relating to their roles in cattle productivity. The objective of this study was to examine the effects of silage and probiotics on ruminal ecosystems in vivo using a molecular approach. Terminal-restriction fragment-length-polymorphism (T-RFLP) analysis was used to detect changes of ecological communities based on 16S-ribosomal deoxyribonucleic acid (16S-rDNA). Two rumen canulated PO cattle were fed several diets i.e.; (R0) basal diet dry matter basis (Pennisetum purpureum 70% and commercial concentrate 30%), (R1) silage (basal diet fermented using Lactobacillus plantarum BTCC570), (R2) silage + probiotics (L. plantarium Str BTCC531), (R3) Basal diet + probiotics (L. plantarium Str BTCC531). Digesta samples were collected 3 h after feeding for pH and T-RFLP analysis. T-RFLP analysis was performed using the 16S-rDNA amplified from each sample. The lengths of the terminal restriction fragments were analysed after digestion with HhaI, HaeIII and MspI. Results showed the effectivenes of silage and probiotics, given together, on the index of Smith and Wilson evenness applied to T-RFLP ecology data (Evar) with 0.89±0.04 being the highest. The diversity of rumen microorganisms is influenced by individual differences of each animal. T-RFLP analysis has a potency to be used for comparisons of complex bacterial communities, especially to detect changes in community structure in response to different variables and to show rumen bacteria diversity in the rumen.